2021
DOI: 10.1155/2021/3795831
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Mild Steel under Canola Biolubricant Conditions

Abstract: New lubricants based on vegetable oil were developed in this study. Different blends of canola oil mixed with fully synthetic two stock engine oils were developed (0, 20%, 40%, 60%, and 80% of synthetic oil).  The viscosity of the prepared blends was determined at different temperatures (20°C–80°C). Tribological experiments were conducted to investigate the effect of the newly developed oil on the wear characteristics of mild steel material compared with stainless steel when subjected to adhesive wear loading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Shalwan et al, [9] conducted tribological performance of different canola blended oil. The outcome showed that pure canola oil as a lubricant performed competitively against a blend of 80% synthetic and 20% canola oils.…”
Section: Introductionmentioning
confidence: 99%
“…Shalwan et al, [9] conducted tribological performance of different canola blended oil. The outcome showed that pure canola oil as a lubricant performed competitively against a blend of 80% synthetic and 20% canola oils.…”
Section: Introductionmentioning
confidence: 99%
“…Even industrial applications like bearings, flooring materials, and brake pads require friction coefficient and Wear RESEARCH resistance [4]. The demand for polymer composite reinforced natural fibres has attained attention as these have excellent environmental properties, which are affordable and easy to manufacture than synthetic fibres [5,6]. Due to these excellent properties, polymer composites are used in the construction, automobile and furniture industries [7].…”
Section: Introductionmentioning
confidence: 99%